Partie orientale de la Nouvelle France ou du Canada avec l'Isle de Terre-Neuve et de Nouvelle Ecosse, Acadie et Nouv. Angleterre avec fleuve St. Laurence - Lotter, Tobias Conrad, 1717-1777 ([Augsburg], 1756)
Hand coloured. Compass rose. Decorative title cartouche. Relief shown pictorially. Vignette in lower right corner. Bar scales in common French leagues, and English and French marine leagues. "Dresse par Alb. Charl. Seutter, geog." (bottom left corner). CNS map no. 229. Date from NMC catalogue.